Therapeutic effect of ursolic acid in experimental visceral leishmaniasis. Issue 1 (April 2017) - Jesus, Jéssica A.; Fragoso, Thais N.; Yamamoto, Eduardo S.; Laurenti, Márcia D.; Silva, Marcelo S.; Ferreira, Aurea F.; Lago, João Henrique G.; Gomes, Gabriela S.; Passero, Luiz Felipe D.
Abstract: Leishmaniasis is an important neglected tropical disease, affecting more than 12 million people worldwide. The available treatments are not well tolerated and present diverse side effects in patients, justifying the search for new therapeutic compounds. In the present study, the therapeutic potential and toxicity of ursolic acid (UA), isolated from the leaves of Baccharis uncinella C. DC. (Asteraceae), were evaluated in experimental visceral leishmaniasis. To evaluate the therapeutic potential of UA, hamsters infected with L. (L.) infantum were treated daily during 15 days with 1.0 or 2.0 mg UA/kg body weight, or with 5.0 mg amphotericin B/kg body weight by intraperitoneal route. Fifteen days after the last dose, the parasitism of the spleen and liver was stimated and the main histopathological alterations were recorded. The proliferation of splenic mononuclear cells was evaluated and IFN-γ, IL-4, and IL-10 gene expressions were analyzed in spleen fragments. The toxicity of UA and amphotericin B were evaluated in healthy golden hamsters by histological analysis and biochemical parameters. Animals treated with UA had less parasites in the spleen and liver when compared with the infected control group, and they also showed preservation of white and red pulps, which correlate with a high rate of proliferation of splenic mononuclear cells, IFN-γ mRNA and iNOS production. Moreover, animals treated with UA did not present alterations in the levels of AST, ALT, creatinine and urea. Taken together, these findings indicate that UA is an interesting natural compound that should be considered for the development of prototype drugs against visceral leishmaniasis. Graphical abstract: Highlights: Animals treated with UA had less parasites in the spleen and liver. Animals treated with UA showed histological preservation of spleen and liver. Animals treated with UA up-regulated the expression of IFN-γ mRNA and iNOS production. UA was not toxic for experimental animals.